2009
DOI: 10.1016/j.cancergencyto.2009.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and conventional cytogenetic characterization of three gastric cancer cell lines

Abstract: Gastric cancer is the fourth most frequent type of cancer and the second most frequent cause of cancer mortality worldwide. Only a modest number of gastric carcinoma cell lines have been isolated thus far. Here we describe the establishment and cytogenetic characterization of three new gastric cancer cell lines obtained from primary gastric adenocarcinoma (ACP02 and ACP03) and cancerous ascitic fluid (AGP01) of individuals from northern Brazil. ACP02, ACP03, and AGP01 cell lines are presently in the 60th passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 42 publications
6
42
1
Order By: Relevance
“…Gains of chromosome 8, either trisomies or polysomies, are among the most common alterations found in malignant gastric tumors (2,3) and in cell lines obtained from them, as previously described by our group in a population of Northern Brazil (14) and in four GC cell lines (4,9). Overamplification of c-MYC was found in 86% of the PG100 cells analyzed by FISH, confirming previous findings.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Gains of chromosome 8, either trisomies or polysomies, are among the most common alterations found in malignant gastric tumors (2,3) and in cell lines obtained from them, as previously described by our group in a population of Northern Brazil (14) and in four GC cell lines (4,9). Overamplification of c-MYC was found in 86% of the PG100 cells analyzed by FISH, confirming previous findings.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, few cell lines originated from gastric tumors are available, and most of them are from Asia (4). Our research group characterized the first GC cell line in Brazil, called ACP01, and recently established and characterized three new GC cell lines (4,9).…”
mentioning
confidence: 99%
“…In this study, most of the copy number changes observed in ACP02, ACP03, AGP01 and PG100 by cCGH were confirmed by aCGH. ACP02, ACP03 and AGP01 are gastric adenocarcinoma cell lines from diffuse and intestinal types and cancerous ascitic fluid and were previously established and characterized by our research group[17,18], while PG100 is a commercially available primary gastric adenocarcinoma cell line[19]. Furthermore, aCGH analysis enabled the identification of many additional chromosomal gains and losses.…”
Section: Discussionmentioning
confidence: 99%
“…The ACP02, ACP03 and AGP01 gastric adenocarcinoma cell lines, which were previously established and characterized by our research group, were used in the present study[17,18]. Additionally, we used the GC cell line, PG100, obtained from the Rio de Janeiro Cell Bank (Rio de Janeiro, RJ, Brazil), which was previously characterized cytogenetically by our group[19].…”
Section: Methodsmentioning
confidence: 99%
“…Our group has previously reported the presence of chromosome 17 aneuploidy, both gains and losses, in GC in individuals in Northern Brazil [3], [4], [5], [6] and in all GC cell lines established from neoplasias in this population [7], [8]. Therefore, this chromosome may contain important genes involved in gastric carcinogenesis.…”
Section: Introductionmentioning
confidence: 97%